An iterative process for verification of a meteorological data server. (October 2013) - Thoman, David; Henley, Elizabeth Raley; O'Kula, Kevin; Davis, Frederick; Morris, James
Key aspects of the verification performed on US Army Dugway Proving Ground (DPG) WeatherServer (WXS) are described. WXS is a Test and Training Enabling Architecture (TENA)-based modeling and simulation that distributes three-dimensional meteorological data over time to participants in a distributed test event or joint exercise environment. The verification features an iterative process as an effective measure to reduce time and costs while still allowing a comprehensive review. In addition, the unique role that WXS serves in efficiently providing real-time meteorological data to support Test and Evaluation (T&E) exercises is discussed. The verification process demonstrated the fidelity of the WXS output and the correctness of the coded technical algorithms (e.g., altitude-to-pressure conversions). The iterative process involved cycles of testing and improved software builds that continued until a build of WXS was developed that functioned as designed. Insights obtained during the iterative process applied to the WXS verification included realizing the full benefits of (1) periodic communications and issue resolution among the developer, verification team, and sponsor; (2) allocating sufficient budget for the software developer's time to support the verification process; and (3) strategically customizing the verification process to allow for an efficient testing and review process following applicable standards.